(H3O)2NaAl3F12, isostructural with A2NaAl3F12 (A = K+, Rb+, Cs+) fluorides having HTB‐type sheets. Issue 5 (15th May 2014) - Jouffret, Laurent; Lhoste, Jerome; Hemon‐Ribaud, Annie; Leblanc, Marc; Maisonneuve, Vincent
<x xml:space="preserve">Abstract</x> The title compound, (H3O)2NaAl3F12 [dihydronium sodium trialuminum(III) dodecafluoride], was obtained by solvothermal synthesis from the reaction of aluminium hydroxide, sodium hydroxide, 1, 2, 4‐triazole and aqueous HF in ethanol at 463 K for 48 h. The structure consists of AlF6 octahedra organized in [AlF4−]n HTB‐type sheets (HTB is hexagonal tungsten bronze) separated by H3O+ and Na+ cations.